CRISPR‐Cas Expands Dynamic Range of Gene Expression From T7RNAP Promoters. Issue 5 (6th December 2017) - McCutcheon, Sean R.; Chiu, Kwan Lun; Lewis, Daniel D.; Tan, Cheemeng
Abstract : Reducing leaky gene expression is critical for improving protein yield of recombinant bacteria and stability of engineered cellular circuits in synthetic biology. Leaky gene expression occurs when a genetic promoter is not fully repressed, leading to unintended protein synthesis in the absence of stimuli. Existing work have devised specific molecular strategies for reducing leaky gene expression of each promoter. In contrast, we describe a repurposed, modular CRISPRi system that attenuates leaky gene expression using a series of single‐guide RNAs targeting the PT7/LacO1 promoter. Furthermore, we demonstrate the efficacy of CRISPRi to significantly increase the dynamic range of T7 RNA Polymerase (T7RNAP) promoters. In addition, we demonstrate that the CRISPRi system can be applied to enhance growth of bacteria that suffer from leaky expression of a toxic protein. Our work establishes a new application of CRISPRi in genomic engineering to improve the control of recombinant gene expression. The approach is potentially generalizable to other gene expression system by changing the single‐guide RNAs. Abstract : A promoter is typically "leaky" even when it is in an OFF state without the required stimulus. The leaky promoter activity hampers growth of recombinant cells, limits protein yield, and hinders the construction of complex genetic circuits in synthetic biology. A CRISPR‐Cas‐based system (i.e., CRISPR‐lim) that reduces leaky promoter activity is developed. The system is modular and may be reprogrammed easily for broad range of promoters.